A Rapid, High Frequency Regeneration of Justicia gendarussa Burm.f. (Bangladesh Journal of Scientific and Industrial Research, 2011)
An efficient plant regeneration protocol was developed for Justicia gendarussa Burm.f. (Acanthaceae), an important medicinal shrub. Nodal segments grown on Murashige and Skoog (MS) medium containing 1.0 mg/l Benzyl adenine (BAP) with 10 % coconut milk showed better growth response and produced 10.5 ± 0.6 shoots per explant with an average length of 4.4 ± 0.3 cm after 35 days. Rooting of shoots was achieved on growth regulator free half strength MS medium produced 5.3 ± 0.25 cm roots with an average height of 4.8 ± 0.2 cm after 30 days. The rooted plantlets were transferred for hardening, 80 % of plants were successfully established in the field. Key words: Justicia gendarussa; Nodal segments; Regeneration; Coconut milk. DOI: http://dx.doi.org/10.3329/bjsir.v46i2.4388 Bangladesh J. Sci. Ind. Res. 46(2), 201-204, 2011